Identification of a Rare Branch Point Variant in the SMS Gene in a Large Family With a Severe Form of Snyder–Robinson Syndrome - Civit, Antoine; Ronce, Nathalie; Cogné, Benjamin; Besnard, Thomas; Laurenceau, David; Hubert, Catherine; Moizard, Marie‐Pierre; Gueguen, Paul; Toutain, Annick; Vuillaume, Marie‐Laure (Clinical genetics, 2025)
Identification of the first pathogenic branch point variant in the SMS gene in a large French non‐consanguineous family with a phenotype retrospectively consistent with Snyder–Robinson syndrome. RT‐PCR analysis followed by RNA‐sequencing demonstrated that this variant, lead to the synthesis of a predominant aberrant transcript with complete intron 6 retention.